Anti-Obfuscation Techniques: Recent Analysis of Malware Detection - Gorment N.Z.; Selamat A.; Krejcar O. (IOS Press BV, 2023)
Machine learning; Malware; Analysis tools; Anti virus; Anti-obfuscation; Comparatives studies; Machine learning algorithms; Malware analysis; Malware detection; Malwares; Obfuscation technique; Stealthy malware; Learning algorithms